A comparison of iodinated trihalomethane formation from chlorine, chlorine dioxide and potassium permanganate oxidation processes. (1st January 2015) - Zhang, Tian-Yang; Xu, Bin; Hu, Chen-Yan; Lin, Yi-Li; Lin, Lin; Ye, Tao; Tian, Fu-Xiang
Abstract: This study compared the formation of iodinated trihalomethanes (I-THMs) from iodide-containing raw waters oxidized by chlorine, chlorine dioxide (ClO2 ) and potassium permanganate (KMnO4 ) at different oxidant concentrations, reaction times, pHs, initial iodide concentrations and bromide to iodide mass ratios. Among the six investigated I-THMs, iodoform was the major species formed during the oxidation using chlorine, ClO2 and KMnO4 . When oxidant concentration increased from 0.1 to 3.0 mg/L, the formation of I-THMs increased and then decreased for chlorine and ClO2, but kept increasing for KMnO4 . As the reaction time went by, I-THM concentration increased to a plateau within 10 h (ClO2 within only 1 h, especially) for all the three oxidants. I-THM formation gradually increased from pH 3.0 to 9.0 and remained stable at pH values higher than 7.5 for chlorine; however, for ClO2 and KMnO4 the highest I-THM formation showed at pH 7.0 and 7.5, respectively. As initial iodide concentration increased from 20 to 800 μg/L, the total amount and species of I-THMs increased for the three oxidants. Iodide contributed to I-THM formation much more significantly than bromide. Graphical abstract: Highlights: The total amount and species of I-THMs decreased in the order of Cl2 > ClO2 > KMnO4 . I-THM formation increased to a plateau within 10 h for all the three oxidants. I-THM peak yields for Cl2, ClO2 and KMnO4 were at pH 7.5–9.0, 7.0 and 7.5, respectively. Iodide contributed to I-THM formation much more significantly than bromide.